The Impact of Between Depression, Anxiety, And Stress on Academic Performance among University Students - Zubairi, Az Athirah; Nasharudin, Nurul Ain Salshabilla; Ibrahim, Mohammad Kamil (Jurnal Pendidikan Bitara UPSI, 2025)
Depression, stress, and anxiety can all have an impact on academic performance through influencing students’ cognitive functioning, self-esteem, and social isolation. The objective of this study is to examine the relationship between depression, anxiety, and stress with academic performance among university students. A total of 166 university students participated in this study, responding to two key questionnaires. The Depression, Anxiety, and Stress Scale (DASS-21) comprising 21 items developed by Lovibond, P. F., and S.H. Lovibond (1995) was utilized alongside 8 questions related to academic performance. The findings revealed there was a negative correlation between depression, stress, and anxiety levels and academic performance. The findings underscore the detrimental impact of psychological distress on students’ educational outcomes. The implications of these findings call for a holistic approach to student wellbeing by monitoring students’ mental health regularly and aiding students in overcoming life’s challenges.